The trefoil with single fruit sign in muscle magnetic resonance imaging is highly specific for dystrophinopathies. Issue 10 (October 2015) - Zheng, Yiming; Li, Wenzhu; Du, Jing; Jin, Suqin; Li, Shanglin; Zhao, Yawen; Xu, Chunxiao; Wang, Zhaoxia; Lv, He; Zhang, Wei; Xiao, Jiangxi; Yuan, Yun
Highlights: The trefoil with single fruit sign is a highly specific finding in dystrophinopathies. The sensitivity of the sign is dependent on the patient's age. Abstract: Background: The purpose of this study was to evaluate the diagnostic value of the trefoil (three leaflets formed by relative sparing of the sartorius, gracilis, and adductor longus) with single fruit sign (relative sparing of the semitendinosus) in the evaluation of thigh muscle magnetic resonance imaging (MRI) for dystrophinopathies. Methods: Five examiners blinded to any clinical data analyzed muscle MRI scans from 166 patients with dystrophinopathies (124 cases confirmed genetically and 42 cases confirmed by immunohistochemistry) and from 244 control patients, all treated in our hospital from 2011 to 2014. The controls were patients with other neuromuscular disorders and with dystrophinopathies excluded by genetic testing and/or muscle biopsy. Examiners assessed the presence or absence of the trefoil with single fruit sign approximately at the middle thigh cross-section. Results were analyzed for diagnostic accuracy and inter-examiner agreement. Results: Sensitivity of the trefoil with single fruit sign for all patients with dystrophinopathies was 41.6% (95% confidence interval (CI) of 34.0–49.5). However, specificity was 99.2% (95% CI 97.1–99.9). The positive predictive value (PPV) was 97.2% and negative predictive value (NPV) was 71.4%. Inter-examiner agreement was substantial (Kappa = 0.66). The 69 dystrophinopathy patients whose MRIs exhibited the sign were significantly older than the 97 dystrophinopathy patients whose MRIs did not ( Z  = −3.970, P  < 0.001). Conclusions: The trefoil with single fruit sign is a potential imaging marker for diagnosis of dystrophinopathies.